Wasp venomic: Unravelling the toxins arsenal of Polybia paulista venom and its potential pharmaceutical applications - Perez-Riverol, Amilcar [UNESP] (2017)
Polybia paulista (Hymenoptera: Vespidae) is a neotropical social wasp from southeast Brazil. As most social Hymenoptera, venom from P. paulista comprises a complex mixture of bioactive toxins ranging from low molecular weight compounds to peptides and proteins. Several efforts have been made to elucidate the molecular composition of the P. paulista venom. Data derived from proteomic, peptidomic and allergomic analyses has enhanced our understanding of the whole envenoming process caused by the insect sting. The combined use of bioinformatics, -omics- and molecular biology tools have allowed the identification, characterization, in vitro synthesis and recombinant expression of several wasp venom toxins. Some of these P. paulista - derived bioactive compounds have been evaluated for the rational design of antivenoms and the improvement of allergy specific diagnosis and immunotherapy. Molecular characterization of crude venom extract has enabled the description and isolation of novel toxins with potential biotechnological applications. Here, we review the different approaches that have been used to unravel the venom composition of P. paulista. We also describe the main groups of P. paulista - venom toxins currently identified and analyze their potential in the development of component-resolved diagnosis of allergy, and in the rational design of antivenoms and novel bioactive drugs.